Bangladesh at 25 : an analytical discourse on development - Bayes, Abdul; Ānu Muhāmmada. (Dhaka : University Press Ltd., 1998)
Papers presented at a seminar organized by the Jahangirnagar University in 1995 to observe 25 years of Bangladesh.
Includes bibliographical references and index.
Keywords: Bangladesh -- Economic conditions -- Congresses; Bangladesh -- Politics and government -- 1971- -- Congresses; Bangladesh -- Social conditions -- Congresses